Fitting, or How Things Arrange Themselves - Nicholas Boyarsky (Oz, 2014)
Questions about complexity in architecture always leave me somewhat bemused. If one does ascribe to the view that architecture is there to provide answers to problems and that there are clearly prescribed methods and rules to deliver it, then one can, I assume, inhabit and work within a world of simplicity, happily innocent and always doint the right thing.